2018
DOI: 10.1016/j.jiph.2017.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Leptospira kmetyi from residential areas of patients with leptospirosis in Kelantan, Malaysia

Abstract: More than one species of Leptospira may be present in a sampling area. The most common environmental isolates were pathogenic L. kmetyi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This species was initially isolated and described in human leptospirosis in Thailand [52] and has also been isolated from animals [53]. In Malaysia, earlier reports described the isolation of L. wolffii from soils and waters in residential areas of patients with leptospirosis [54], market and recreational areas [55]. This also further illustrates the contribution of Leptospira from the "intermediate" cluster as causes of human leptospirosis.…”
Section: Discussionmentioning
confidence: 80%
“…This species was initially isolated and described in human leptospirosis in Thailand [52] and has also been isolated from animals [53]. In Malaysia, earlier reports described the isolation of L. wolffii from soils and waters in residential areas of patients with leptospirosis [54], market and recreational areas [55]. This also further illustrates the contribution of Leptospira from the "intermediate" cluster as causes of human leptospirosis.…”
Section: Discussionmentioning
confidence: 80%
“…This indicated that a significant proportion of water sources contained Leptospira. The usual recommendations for avoiding Leptospira infection include wearing boots and thorough washing after work; however, this may not be sufficient given that both water sources around residential areas and those outside, in areas of work, may be contaminated [34,35]. In addition, the large differences observed between our study sites in terms of water contact patterns (including sharing of water sources) highlights the need for leptospirosis surveillance, prevention, and control strategies that take local environmental and behavioral factors into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…In New Caledonia, the biodiversity of Leptospira isolated from soil has been revealed recently by identifying 12 novel species using MALDI-ToF mass spectrum and whole-genome sequencing analysis [6]. Using culture techniques and DNA detection, Leptospira has also been found in environmental samples from Malaysia [111,115]. In the same country, pathogenic Leptospira were recovered from soil washings in the early 1960s using animal inoculation.…”
Section: Leptospira In the Soil Environmentmentioning
confidence: 99%
“…Stagnant water vs soil (19% vs 67%) [115] Minesotta, USA Lake shore water vs soil (65% vs 75%) [9] Bog water vs soil (5% vs 44%)…”
Section: Malaysiamentioning
confidence: 99%